Inhibition of integrin β3, a binding partner of kallistatin, leads to reduced viability, invasion and proliferation in NCI-H446 cells. Issue 1 (December 2016) - Wang, Guoquan; Wang, Xiao; Huang, Xiaoping; Yang, Huiyong; Pang, Suqiu; Xie, Xiaolan; Zeng, Shulan; Lin, Junsheng; Diao, Yong
Abstract Background Kallistatin is a serine proteinase inhibitor and heparin-binding protein. It is considered an endogenous angiogenic inhibitor. In addition, multiple studies demonstrated that kallistatin directly inhibits cancer cell growth. However, the molecular mechanisms underlying these effects remain unclear. Methods Pull-down, immunoprecipitation, and immunoblotting were used for binding experiments. To elucidate the mechanisms, integrin β3 knockdown (siRNA) or blockage (antibody treatment) on the cell surface of small the cell lung cancer NCI-H446 cell line was used. Results Interestingly, kallistatin was capable of binding integrin β3 on the cell surface of NCI-H446 cells. Meanwhile, integrin β3 knockdown or blockage resulted in loss of antitumor activities induced by kallistatin. Furthermore, kallistatin suppressed tyrosine phosphorylation of integrin β3 and its downstream signaling pathways, including FAK/-Src, AKT and Erk/MAPK. Viability, proliferation and migration of NCI-H446 cells were inhibited by kallistatin, with Bcl-2 and Grb2 downregulation, and Bax, cleaved caspase-9 and caspase 3 upregulation. Conclusions These findings reveal a novel role for kallistatin in preventing small cell lung cancer growth and mobility, by direct interaction with integrin β3, leading to blockade of the related signaling pathway.